Concomitant Imperforate Hymen and Transverse Vaginal Septum Complicated with Pyocolpos and Abdominovaginal Fistula - Berna Dilbaz; Sadiman Kiykac Altinbas; Namik Kemal Altinbas; Ozlem Sengul; Serdar Dilbaz (Case Reports in Obstetrics and Gynecology)
A 13-year-old patient with a complaint of worsening lower abdominal pain during the past 4 months was admitted to the emergency department. An abdominopelvic ultrasound scan revealed a distended uterocervical cavity suggestive of hematometrocolpos. Imperforate hymen was observed on examination of the external genitalia. MRI scan revealed an air-fluid level representing pyometrocolpos within a distended vagina. Posterior vaginal extraperitoneal leakage as the sign of a fistula between the vagina and the rectovaginal space was detected. Although laparoscopic approach was planned, malodorous pus expelled after the insertion of the Veress needle, it was decided to proceed to laparotomy. Pus with peritoneal microabscess formations was observed at laparotomy. The imperforate hymen and TVS were excised vaginally. A more complex anomaly should be suspected in cases with hematometra and concomitant imperforated hymen without any bulging and thorough evaluation using radiological imaging techniques should be performed before surgical approach.